Bahasa Melayu abad ke-16 satu analisis berdasarkan teks Melayu ʻAqaʼid al-Nasafi - Asmah Haji Omar 1940-; Al-Nasafī, ̕Umar ibn Mụhammad 1068?-1142. (Kuala Lumpur Dewan Bahasa dan Pustaka, Kementerian Pendidikan Malaysia, 1991)
Analysis of the 16th century Malay language, based on the Malay text of ʻAqaid al-Nasafi.
In Malay.
Includes bibliographical references (pages 147-148).
Keywords: Malay language -- History